Critical Analysis of Non-Thermal Plasma-Driven Modulation of Immune Cells from Clinical Perspective - Smolková, Barbora; Frtús, Adam; Uzhytchak, Mariia; Lunova, Mariia; Kubinová, Šárka; Dejneka, Alexandr; Lunov, Oleg (International journal of molecular sciences, 2020)
The emerged field of non-thermal plasma (NTP) shows great potential in the alteration of cell redox status, which can be utilized as a promising therapeutic implication. In recent years, the NTP field considerably progresses in the modulation of immune cell function leading to promising in vivo results. In fact, understanding the underlying cellular mechanisms triggered by NTP remains incomplete. In order to boost the field closer to real-life clinical applications, there is a need for a critical overview of the current state-of-the-art. In this review, we conduct a critical analysis of the NTP-triggered modulation of immune cells. Importantly, we analyze pitfalls in the field and identify persisting challenges. We show that the identification of misconceptions opens a door to the development of a research strategy to overcome these limitations. Finally, we propose the idea that solving problems highlighted in this review will accelerate the clinical translation of NTP-based treatments.
Keywords: Immunity, Cellular; Signal Transduction; regulace genové exprese; lidé; Gene Expression Regulation; buněčná imunita; plazmové plyny; signální transdukce; Plasma Gases; Humans